Makna Prosesi Kalengkano Pogau Pada Adat Perkawinan Muna Di Kel. Benua Nirae Kec. Abeli Kota Kendari - Ashar Hasyim; La Ode M. Nasir (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
The problem in this study is what is the meaning of the Cankano Pogau procession in the Muna marriage custom. The purpose of this research is to find out the meaning of the Cankano Pogau procession in the Muna wedding custom. The benefits of this research are theoretically: this research is expected to add and broaden insights about the meaning of semiotics, practically: this research is expected to provide input to the community who will later become traditional leaders, methodologically: this research can be used as additional information material for researchers furthermore in order to enrich the results of research, especially regarding traditional marriages of the Muna people.The subjects in this study were traditional leaders and religious leaders as well as the local community who clearly knew about the Cankano Pogau procession. The technique of recruiting informants in this study was carried out by means of a purposive sampling technique, namely choosing deliberately by considering that the informant concerned knew and fully understood the essence of the problem, with a total of 8 informants. The data collected was analyzed using semiotic analysis.The results of this study indicate that the Muna people of Benua Nirae Village use the Cankankano Pogau Procession as a reference in a traditional marriage process. Based on the research that has been done, the meaning contained in the Cankankano Pogau procession is the Cankankano Pogau procession is a form of appreciation or respect for the male family to the female family in a Muna community marriage process.